Examining the existence of bound states in a square well using a simple method - Perles, João Vitor Santos [UNESP]; Filho, Elso Drigo [UNESP] (FapUNIFESP (SciELO), 2023)
The time-independent Schrödinger equation is analytically solved for the square, one-dimensional and symmetrical potential well, in order to demonstrate, using a simple method, that there is at least one bound state in the limiting cases of depth and width of the analyzed system. For a complete analysis, five conditions for the depth and width of the well are required.
Examinando a existência de estados ligados em um poço quadrado aplicando um método simples
Keywords: Bound states; Potential well; Schrödinger equation